Defining successful outcomes and preferences for clinical management in differences/disorders of sex development: Protocol overview and a qualitative phenomenological study of stakeholders' perspectives. Issue 1 (February 2022) - Suorsa-Johnson, Kristina I.; Gardner, Melissa D.; Baskin, Alison; Gruppen, Larry D.; Rose, Angela; Rutter, Meilan M.; Schafer-Kalkhoff, Tara; Stacey, Dawn; van Leeuwen, Kathleen D.; Weidler, Erica M.; Sandberg, David E.
Summary: Introduction: Utilizing a qualitative phenomenological design, the Defining Successful Outcomes and Trade-offs study examined stakeholder perspectives regarding optimal healthcare delivery and outcomes for individuals with a difference/disorder of sex development (DSD). Objective: We describe study methods and provide an overview of themes and subthemes. Study design: Interviews were conducted with individuals with a DSD (n = 24), parents of those with a DSD (n = 19), healthcare providers (n = 37), and others (n = 30). Primary questions regarding clinical management of patients with DSD were: "What is a successful outcome?" and "How do you achieve it?" Results: Themes included: understanding of DSD diagnosis and self-efficacy in management is necessary but complex; patient and family psychological well-being; support from others versus being stigmatized; affected person experiences physical health and accepts the implications of their condition; complexities in DSD decision making, roles and expectations; and knowledgeable providers and multidisciplinary teams are essential, notwithstanding persisting barriers. Participants recognized competing values potentially forcing trade-offs in decision making. Discussion: Recognition of diverse and sometimes conflicting perspectives regarding optimal pathways of care and outcomes – both within and among those with DSD and their providers –promises to enhance shared decision making. Conclusion: Diverse perspectives and perceptions of trade-offs associated with DSD healthcare emphasize the need to tailor care for patients and families. Summary Figure. Identified Themes. Note . DSD = difference/disorder of sex development. Summary Figure